How phenotypic convergence arises in experimental evolution. (31st July 2019) - Simões, Pedro; Fragata, Inês; Santos, Josiane; Santos, Marta A.; Santos, Mauro; Rose, Michael R.; Matos, Margarida
Abstract: Evolutionary convergence is a core issue in the study of adaptive evolution, as well as a highly debated topic at present. Few studies have analyzed this issue using a "real‐time" or evolutionary trajectory approach. Do populations that are initially differentiated converge to a similar adaptive state when experiencing a common novel environment? Drosophila subobscura populations founded from different locations and years showed initial differences and variation in evolutionary rates in several traits during short‐term (∼20 generations) laboratory adaptation. Here, we extend that analysis to 40 more generations to analyze (1) how differences in evolutionary dynamics among populations change between shorter and longer time spans, and (2) whether evolutionary convergence occurs after 60 generations of evolution in a common environment. We found substantial variation in longer term evolutionary trajectories and differences between short‐ and longer term evolutionary dynamics. Although we observed pervasive patterns of convergence toward the character values of long‐established populations, populations still remain differentiated for several traits at the final generations analyzed. This pattern might involve transient divergence, as we report in some cases, indicating that more generations should lead to final convergence. These findings highlight the importance of longer term studies for understanding convergent evolution.